Knowledge management as a determinant of job satisfaction - Ćurčić Mihailo; Matejić Ivica (Trendovi u Poslovanju)
The development of technics, technology, communication and traffic has contributed to all organizations having the same or similar material resources that they use in the process of work. The difference between organizations is reflected in human resources, ie., employees. Employees are not enough to outperform the competition. Establishing a leadership position over competitors requires employees who possess knowledge, abilities and skills that are critical to the success of the organization. For this reason, more and more organizations are focusing on identifying, training and retaining employees with "critical knowledge". For the success of the organization in this regard, it is necessary to have a developed knowledge management system in the work environment. The aim of the research in this paper is to identify the interdependence of elements that determine the processes of knowledge management and job satisfaction. The empirical research was conducted in 2021 in the organizational units of the Ministry of Defense of the Republic of Serbia on a sample of 58 respondents, using the survey method. The results of the research show that there is an interdependence between the observed parameters, and their interpretation is presented in the paper itself.